Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3892/ol.2019.11077
|View full text |Cite
|
Sign up to set email alerts
|

CDKN3 promotes cell proliferation, invasion and migration by activating the AKT signaling pathway in esophageal squamous cell carcinoma

Abstract: In China, esophageal squamous cell carcinoma (ESCC), capable of direct invasion and early metastasis, exhibits high mortality. Identification of the molecular basis driving ESCC progression and development of new diagnostic biomarkers are urgently needed. Cyclin-dependent kinase inhibitor 3 (CDKN3) performs crucial roles in the modulation of tumor development. The present study aimed to explore the functions and underlying mechanism of CDKN3 in regulating ESCC cell proliferation and invasion. The expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…Besides, our immunohistochemical study indicated that there is an abnormal expression of CDKN3 protein in ESCC patients, which preliminarily con rmed its association with the progress of ESCC. Meanwhile, recent studies suggested that CDKN3 is partly responsible for the proliferation, invasion and metastasis of esophageal squamous cell carcinoma via AKT sign pathway dependently or independentl, which also is a corroborative evidence for the reliability of our study [17,18].…”
Section: Discussionsupporting
confidence: 88%
“…Besides, our immunohistochemical study indicated that there is an abnormal expression of CDKN3 protein in ESCC patients, which preliminarily con rmed its association with the progress of ESCC. Meanwhile, recent studies suggested that CDKN3 is partly responsible for the proliferation, invasion and metastasis of esophageal squamous cell carcinoma via AKT sign pathway dependently or independentl, which also is a corroborative evidence for the reliability of our study [17,18].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have found that the AKT pathway is one of the main signaling pathways in uencing cancer cell proliferation. [24][25][26][27][28][29] Therefore, it was reasonable to consider that STEAP1 can affect cell proliferation via the AKT pathway. Our results also showed that when STEAP1 was downregulated, P-AKT, CDK4, and Cyclin D1 were relatively downregulated, and P27 and P-FoxO1 were upregulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN3 is reported to be involved in the occurrence and development of some types of tumors [27,28]. CDKN3 facilitated the promotion of ESCC cell proliferation, invasion and migration by activating the AKT signaling pathway [29]. CDKN3 knockdown significantly inhibited ESCC cell proliferation, migration, and invasion, and suppressed the G1 / S transition of tumor cells, providing a potential target for ESCC treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN3 facilitated the promotion of ESCC cell proliferation, invasion and migration by activating the AKT signaling pathway [29]. CDKN3 knockdown significantly inhibited ESCC cell proliferation, migration, and invasion, and suppressed the G1 / S transition of tumor cells, providing a potential target for ESCC treatment [29]. RAD51-associated protein 1 (RAD51AP1) is an emerging protein that is essential for RAD51-mediated Homologous recombination (HR).…”
Section: Discussionmentioning
confidence: 99%